MÍDIA E ELEIÇÕES: O MEIO AMBIENTE NA CAMPANHA PRESIDENCIAL DE 2010 - Carvalho, Gabriel Ferreira (2013)
The present research is an analysis of the environment theme during Brazil’s presidential election in 2010. At that time, there was a candidate from the Green Party, Marina Silva, who received about 20 million votes. In order to do this analysis, this research aims at studying the presence of environmental issues in political articles published during the electoral process in question. The object chosen for analysis were the pages of the newspaper Folha de S. Paulo, which has the largest daily circulation in the country and is set as the public sphere. The research looks at the concerns regarding the environmental issues throughout world history, in Brazil and in politics. The research also presents the main theories underlying the study of journalism, so the articles can be analyzed as journalistic texts by their frameworks, scheduling themed and public opinion. The method used to analyze the articles was Content Analysis, which employs categories to identify in the texts speeches that are compatible with the categories (qualitative results) searched. Furthermore, it allows one to check the count and percentage of categories approached in the text (quantitative). At the end, integrated into the results were integrated, leading to the conclusion that the environmental issue was not discussed by the candidates nor the newspaper.